Al-Lu'bah al-Lughawiyyah al-Namudzajiyyah fi Ta'lim al-Kitabah - Widodo, Arif (Universitas Islam Negeri Raden Intan Lampung, 2019)
Language games of teaching Arabic and learning are important to improve the quality of learning outcomes in speaking skills. Generally, the objectives of this research are to know the importance of recreational activities by language games of Arabic. In addition, specifically, it is to know 1) writing skills, 2) language games for writing Arabic, 2) models of fun activities for writing skills. The data are collected by documentation and library research. The data are analyzed by descriptive and content analysis. The results of the research show that 1) the final directions of writing skills are to improve the ability to write official Arabic, 2) spirit, positive emotions and learning activeness can be improved with fun activities, 3) in general, there are seven models of fun activities for Arabic that can be used to improve the learning process becomes fun. The novelty of this research is the tendency of the students to be movement in the movement of comfortable activities.